Non-Invasive Diagnostic Methods Image Processing - Marzec, Mariusz; Koprowski, Robert (Biomedical Engineering, 2018)
The main themes of the book are the broadly understood methods of image analysis and processing applied to support diagnosis and therapy, but also to assess the implants placed in the patient's body and the related treatment processes. The examples concern processing and analysis of images or measured signals obtained from various diagnostic imaging methods. The study used, among others, standard X-ray images, computed tomography images, microtomographic images, as well as thermographic and ultrasound images. The results of image and signal processing were used in medical diagnosis and to evaluate the effectiveness of therapy. The material contained in this book may be of interest to a wide audience, and the discussed topics cover the current state of knowledge on the use of image processing algorithms in medicine and related fields.